2021
DOI: 10.1016/j.bioactmat.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming bacterial physical defenses with molecule-like ultrasmall antimicrobial gold nanoclusters

Abstract: The size of metal nanoparticles (NPs) is crucial in their biomedical applications. Although abundant studies on the size effects of metal NPs in the range of 2–100 nm have been conducted, the exploration of the ultrasmall metal nanoclusters (NCs) of ~1 nm in size with unique features is quite limited. We synthesize three different sized gold (Au) NCs of different Au atom numbers and two bigger sized Au NPs protected by the same ligand to study the size influence on antimicrobial efficacy. The ultrasmall Au NCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 66 publications
(77 reference statements)
3
62
0
Order By: Relevance
“…Atomically precise Au NCs exhibit unique physicochemical properties different from those of their larger counterparts (Au NPs), in which even few atom differences among Au NCs induce huge effects or even contrasting biological behaviors. 54,55 For instance, Zhang et al observed a unique size-dependent nanocatalysis at the single Au NC level. They observed that small Au NCs ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Atomically precise Au NCs exhibit unique physicochemical properties different from those of their larger counterparts (Au NPs), in which even few atom differences among Au NCs induce huge effects or even contrasting biological behaviors. 54,55 For instance, Zhang et al observed a unique size-dependent nanocatalysis at the single Au NC level. They observed that small Au NCs ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Internalization of AuNCs (~1-2 nm) by bacteria has been reported in antibacterial and photosensitizing studies. 82,85 However, the actual pathways that allow higher accumulation of larger clusters compared to the smaller Au 9 -clusters and Au I -complexes warrant further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[239] Our group and others have demonstrated that both ultrasmall Au and Ag NCs can be used as nano-antibiotics for drug-resistant bacteria, indicating their potential in targeted antimicrobial therapy. [80,[240][241][242][243][244][245] There is no doubt that with the development of synthetic chemistry, the library of functional metal NCs will be enriched, and more nanoplatforms based on metal NCs will be developed and widely used to treat various diseases including cancer.…”
Section: Summary and Perspectivesmentioning
confidence: 99%